2014
DOI: 10.1007/s10973-014-3893-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of the calorimetric and spectroscopic methods in analytical evaluation of the human milk fat substitutes

Abstract: The aim of this paper was the analytical evaluation of human milk fat substitutes (HMFS) by the calorimetric and spectroscopic methods. The HMFS were obtained by enzymatic interesterification of blend of lard or milk fat with rapeseed oil and concentrate of fish oil. The enzymatic reactions were carried out at 60, 70, and 80°C for 2 h. A commercially immobilized 1,3-specific lipase, Lipozyme RM IM, was used as a biocatalyst. Oxidative stability of HMFS was determined using the calorimetric method. The oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…Analyzing and comparing the results, the FFA content in mixtures increased after enzymatic interesterification reaction. These results are in agreement with Brys et al [14], who indicated that enzymatic interesterification process caused the increase in FFA amount. The AV and FFA contents depend significantly on the time of the reaction.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Analyzing and comparing the results, the FFA content in mixtures increased after enzymatic interesterification reaction. These results are in agreement with Brys et al [14], who indicated that enzymatic interesterification process caused the increase in FFA amount. The AV and FFA contents depend significantly on the time of the reaction.…”
Section: Resultssupporting
confidence: 93%
“…In the majority of these studies, HMFS resembling HMF were obtained by enzymatic interesterification or acidolysis reactions of tripalmitin or lard with free fatty acids from different sources. Lard has been recommended as a potential alternative because it is the only fat resembling HMF in terms of fatty acid composition [14]. Compared with HMF, lard has a similar palmitic and oleic acids content but is characterized by lower content of essential fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal analysis is convenient and reproducible, and is a useful method for characterizing heterogeneous organic materials [14]. In past decades, differential thermal analyses (DTA), a differential scanning calorimetry (DSC) and thermogravimetric analysis (TG) have been used for analysing biological materials from plants [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Induction time can be used as primary parameter for the assessment of the resistance of tested fats to their thermal oxidative decomposition. Generally, samples with longer induction times are more stable than those for which the induction time obtained at the same temperature is shorter [32][33][34][35][36]. The higher degree of unsaturation of fatty acids makes these fats more susceptible to oxidation processes.…”
Section: Oxidative Stabilitymentioning
confidence: 99%